MULTISPECTRAL MICROSCOPY AND COMPUTERIZED IMAGE ANALYSIS: A METHOD TO OBTAIN MORE RELIABLE AND REPRODUCIBLE IMMUNOHISTOCHEMISTRY RESULTS - Giovanni Francesco Spatola (Euromediterranean Biomedical Journal, 2015)
The use of image analysis methods has allowed us to obtain more reliable and repro-ducible immunohistochemistry (IHC) results. Wider use of such approaches and sim-plification of software allowing a colorimetric study has meant that these methods are available to everyone, and made it possible to standardize the technique by a reliable systems score. Moreover, the recent introduction of multispectral image acquisition systems methods has further refined these techniques, minimizing artefacts and eas-ing the evaluation of the data by the observer.